DESIGN AND IMPLEMENTATION OF AN ENGINE CONTROL UNIT WITH RPM STABILIZATION : ONE-CYLINDER ENGINE GENERATOR APPLICATIONS - Hakim Iskandar, Farhan
In engine-driven generator set system, the electronic control unit must not only manage the functionality of an engine, but also maintain a stable engine RPM under different load. This paper provides a detailed discussion regarding the analysis and results of the design and implementation of an engine control unit for engine-driven generator set. The discussion encompasses end-to-end design process, including circuit design, component selection, PCB layout, and testing. Results demonstrate that the proposed ECU effectively manages engine functions, such as sensor data acquisition, injection and ignition timing calculations, and actuator control. Additionally, the design showcases RPM stabilization capabilities.